The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1115/1.3247039
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Plain and Low-Finned Condenser Tubes—Effect of Fin Spacing and Drainage Strips on Heat Transfer and Condensate Retention

Abstract: The paper reports a continuation of an experimental investigation of the effect of fin pitch on the heat transfer performance of horizontal, integral-fin tubes for condensation of steam at near-atmospheric pressure. The effects of “drainage strips” located along the lower edge of finned and plain tubes have been studied. These gave significant increases in the heat transfer coefficient for finned tubes but had only marginal effect for the plain tube. Condensate retention angles have also been measured for simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Yau et al [14] also used solid drainage strips with two integral-fin tubes of fin spacing of 1.5 and 2.0mm and found that for steam the drainage strip significantly reduced the condensate flooding. The drainage strips were made of copper having a thickness of 0.5mm and a height of 8mm.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yau et al [14] also used solid drainage strips with two integral-fin tubes of fin spacing of 1.5 and 2.0mm and found that for steam the drainage strip significantly reduced the condensate flooding. The drainage strips were made of copper having a thickness of 0.5mm and a height of 8mm.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 99%
“…The effect of fin spacing was investigated on the same set of tubes as used by Yau et al [14,24] with the inclusion of a new integral-fin tube with a fin spacing of 0.25mm. Predetermined coolant-side correlation and a modified Wilson plot method were used to evaluate the vapour-side, heat-transfer coefficients.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller the interfin space, or the larger the surface tension, the bigger the retention angle is [4]. Yau and colleagues [5], using the same method as Hondas, found that the flooding angle (=π-retention angle) was increased for R-113, ethylene glycol, and water by about 10, 20, and 40%, respectively. But, since the structure of the porous drainage strip is relatively complex, it is unsuitable for compact heat transfer exchangers and not easily used.…”
Section: Introductionmentioning
confidence: 97%